Pengaruh Sistem Informasi Akuntansi dan Pengendalian Internal Terhadap Kualitas Laporan Keuangan (studi empiris pada Pemerintah Daerah Kabupaten Solok) - Juita Sukraini; Witra Maison; Sakinah, Hanifatus (Politeknik Raflesia Press, 2025)
This research aims to determine the influence of the Accounting Information System (X1) and Internal Control (X2) on the Quality of Financial Reports (Y). The research results show that there is an influence of the Accounting Information System (X1) on the Quality of Financial Reports (Y). Theresults of testing this first hypothesis are proven bythe value |tcount| amounting to 2.891 > 1.992 and thesignificance value of t is 0.005 < 0.05. After that, there is an influence of Internal Control (X2) on the Quality of Financial Reports (Y). The results of testing this second hypothesis are proven by the value |tcount|amounting to 2.180 > 1.992 and the significance value of t is 0.032 < 0.05. Apart from that, there is an influence of the Accounting Information System (X1) and Internal Control (X2) on the Quality of Financial Reports (Y). The results of testing this third hypothesis are proven by the value |Fcount| amounting to 7,900 > f table 3.12 with a significance value of 0.001 < 0.05.